Synthesis of zigzag- and fjord-edged nanographene with dual amplified spontaneous emission. Issue 44 (31st October 2022) - Xu, Xiushang; Serra, Gianluca; Villa, Andrea; Muñoz-Mármol, Rafael; Vasylevskyi, Serhii; Gadea, Marcos; Lucotti, Andrea; Lin, Zensen; Boj, Pedro G.; Kabe, Ryota; Tommasini, Matteo; Díaz-García, María Á.; et al.
Abstract : Dibenzo[ a, m ]dinaphtho[ ef, hi ]coronene with zigzag and fjord edges was synthesized and characterized, demonstrating a nonplanar structure with near-infrared stimulated emission with a relatively long lifetime and dual-amplified spontaneous emission. Abstract : We report the synthesis of a dibenzodinaphthocoronene (DBDNC) derivative as a novel nanographene with armchair, zigzag, and fjord edges, which was characterized by NMR and X-ray crystallography as well as infrared (IR) and Raman spectroscopies. Ultrafast transient absorption (TA) spectroscopy revealed the presence of stimulated emission signals at 655 nm and 710 nm with a relatively long lifetime, which resulted in dual amplified spontaneous emission (ASE) bands under ns-pulsed excitation, indicating the promise of DBNDC as a near-infrared (NIR) fluorophore for photonics. Our results provide new insight into the design of nanographene with intriguing optical properties by incorporating fjord edges.